Tourist-chatbot interaction in tourist destinations: a comprehensive review - Condori-Chura, Delia (2024)
Tourist-chatbot interaction in tourist destinations is crucial for tourist loyalty. This systematic review article evaluates how the quality and frequency of this interaction influence tourists' perception of usefulness, satisfaction, and loyalty. The relevance of effective communication is highlighted as a fundamental factor to enrich the tourist experience. and encourage loyalty. The objective was to analyze this influence in detail, focusing on the tourist's perception. A systematic review approach was employed to analyze relevant studies in the field. Searches were carried out in relevant databases, such as Web of Science, Scopus and Scielo, following an exhaustive and reproducible protocol using the PRISMA methodology. Limitations in the search and quality of the studies were identified, suggesting future research with larger samples, longitudinal studies and consideration of contextual factors. In conclusion, the quality of the interaction between tourists and chatbots is essential to enhance the tourist experience and visitor loyalty in tourist destinations, highlighting the importance of improving these interactions to raise both the perception of the destination and user satisfaction.